M-Learning-E-Book: Higher Level Thinking Skills, Retention, Motivation of Junior High School Students - Agus Purwowidodo (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
M-Learning-E-Book is an innovative learning model that is relevant to the demands of the twenty-first-century scheme. Studies on M-Learning-E-Book are still not widely conducted by Indonesian researchers and the study is still limited to the effect of this model on student learning outcomes. Therefore, this study aims to examine the effect of M-Learning-E-Book implementation on higher-order thinking skills, retention, and learning motivation. This research used quasi quasi-experimental method through pretest-posttest nonequivalent control group design. The research subjects were students of SMP Negeri Ngunut 1, 2023 academic year, totaling 87 experimental classes and 76 control classes in PAI lessons. In the control class, students followed learning in the form of expository and class discussions, while in the experimental class, students followed learning through E-book-based M-learning. In the experimental class, students met face-to-face for 4 times of online learning equivalent to 4 meetings. The research was conducted when the research subjects in both classes received the topic aspects of islamic history and culture. The instruments used to collect data were higher-order thinking skills test sheets, retention of learning outcomes, and motivation questionnaires. The data obtained were then analyzed using one-way MANOVA analysis with a significance level of 5%. The results showed that the application of M-Learning-E-Book had a significant effect on the achievement of higher-order thinking skills, retention, and learning motivation.  The results of this study indicate that M-Learning-E-Book is one of the learning alternatives that are by the demands of the twenty-first century. Keywords: Higher Level Thinking Skills, Higher-Order Thinking Skills, Motivation